2006
DOI: 10.1002/path.2106
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of CpG island loci and hypomethylation of LINE‐1 and Alu repeats in prostate adenocarcinoma and their relationship to clinicopathological features

Abstract: Promoter CpG island hypermethylation is an important carcinogenic event in prostate adenocarcinoma. Regardless of tissue type, human cancers have in common both focal CpG island hypermethylation and global genomic hypomethylation. The present study evaluated CpG island loci hypermethylation and LINE-1 and Alu repeat hypomethylation in prostate adenocarcinoma, analysed the relationship between them, and correlated these findings with clinicopathological features. We examined 179 cases of prostate adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 33 publications
12
153
3
Order By: Relevance
“…On the other hand, there was no association between LINE-1 methylation and Gleason score. Although this latter finding is not completely inconsistent with previous studies (a clear association between LINE-1 hypomethylation and Gleason score has been found only in one out of 3 previous studies 22,23,26 ), if global methylation was a late event in prostate cancerogenesis, we would have expected higher hypomethylation among patients with a Gleason score of at least 8. It could be speculated that global methylation is more related to the metastatic potential of aggressive prostate cancers than to the Gleason score, and it is of interest that previous studies strongly indicate a decreased global methylation in the prostate cancer tissue among prostate cancer patients with systemic metastases.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…On the other hand, there was no association between LINE-1 methylation and Gleason score. Although this latter finding is not completely inconsistent with previous studies (a clear association between LINE-1 hypomethylation and Gleason score has been found only in one out of 3 previous studies 22,23,26 ), if global methylation was a late event in prostate cancerogenesis, we would have expected higher hypomethylation among patients with a Gleason score of at least 8. It could be speculated that global methylation is more related to the metastatic potential of aggressive prostate cancers than to the Gleason score, and it is of interest that previous studies strongly indicate a decreased global methylation in the prostate cancer tissue among prostate cancer patients with systemic metastases.…”
Section: Discussioncontrasting
confidence: 75%
“…We have recently conducted a systematic review of studies on prostatic tumor global hypomethylation and prostate cancer progression: 19 although studies were heterogeneous and mostly based on a limited sample size, global hypomethylation was reported to be associated with high Gleason score, advanced tumor stage, high pre-operative PSA, and presence of metastasis. [20][21][22][23][24][25][26] The genome-wide methylation level of the long interspersed nuclear element-1 (LINE-1) is considered as a good surrogate marker for global methylation, [27][28][29] as LINE-1 is widely interspersed and represents about 15% of human genome. 30,31 Thus, in the present study we have analyzed prostate tissue LINE-1 methylation status in a cohort of prostate cancer patients in association with Gleason score, gene-specific hypermethylation, and mortality from prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Nakarin Kitkumthorn 1 , Somboon Keelawat 2 *, Prakasit Rattanatanyong 3 , Apiwat Mutirangura 3 tumor metastasis (Cho, 2007;Shuangshoti, 2007;Tangkijvanich, 2007;Pattamadilok, 2008;Iramaneerat, 2011;Kitkumthorn, 2011;Nopavichai, 2012).…”
Section: Line-1 and Alu Methylation Patterns In Lymph Node Metastasesmentioning
confidence: 99%
“…The increase in tumor suppressor gene CpG island methylation between cancerous and noncancerous tissue is often close to 100% (77) and is usually reversed at CpG sites associated with tandemly repetitive and interspersed repeat DNA in the same tumor cells (78)(79)(80)(81). Specific profiles of methylation have also been associated with factors that predict prognosis (82).…”
Section: Epigenetics and Diseasementioning
confidence: 99%